Improving hydration and carbonation of reactive magnesium oxide cement - Tye, Wenkai (2018)
Reactive MgO cement (RMC) formulations had garnered interests as a replacement to Portland Cement, for its low energy consumption during its production and CO2 sequestration abilities. However, mechanical strength advancement of RMC concrete is limited by the low hydration and carbonation of MgO in ambient conditions. Some past studies had presented the effectiveness of using hydrating agents (HA) to improve hydration of MgO while others improved the carbonation aspect via various methods. This study aims to improve hydration and carbonation of RMC concrete simultaneously by combining the use of hydrating agents and enhanced curing techniques. In the first half of the study, the effectiveness of different HAs used were evaluated using isothermal calorimetry, compressive strength test, XRD, TGA and SEM. Magnesium acetate proved to be the most effective by gaining ~80 MPa of compressive strength after 56 days, which was 135% higher than the control mix. It also improved the morphology of the HMCs formed when compared to other mixes. It was then used in the second half of the study, where samples were treated with sodium bicarbonate, high initial curing temperature or by introduction of nano-silica as seeds. Only seeding using nano-silica improved the compressive strength of concrete when compared to the control mix (without use of enhanced curing techniques). It recorded a 12.5% improvement over the control mix after 14 days of curing. Moreover, dense interconnections of HMCs were observed.